Structural Manipulation of a Zirconocene‐Based Porous Coordination Cage Using External and Host–Guest Stimuli. Issue 5 (8th December 2021) - Xiao, Zhifeng; Drake, Hannah F.; Rezenom, Yohannes H.; Cai, Peiyu; Zhou, Hong-Cai
Abstract : Porous coordination cages (PCCs) constructed from a zirconocene‐based cluster have drawn great attention for their high stability and structural tunability. These features have enabled these cages to be utilized for a wide array of applications. This work demonstrates the structural flexibility and stimulus‐responsive features of two interconvertible zirconocene‐based PCCs. The subjects, PCC‐20c (capsular) and PCC‐20t (tetrahedral), are constructed from the same cluster and ligand but exhibit different shapes and properties. In the synthetic study of the cages, it is found that higher temperatures of synthesis yield PCC‐20c in several different crystalline phases while lower temperatures of synthesis yield pure phase PCC‐20t . Thermodynamic studies on the interconversion of the two cages show that the conversion from PCC‐20t into PCC‐20c is an entropically driven process and can be largely affected by the solvent environment. Additionally, the process of PCC‐20t /c conversion can be mediated by the counter anions and light irradiation as evidenced by the change in equilibrium constants under these influences. The current studies are conducted to decipher how the PCC‐20t /c phase can be controllably synthesized, interconverted, and their properties can be modified under the use of external stimuli: heat, light, and guest molecules. Abstract : This work demonstrates a straightforward strategy to control the formation of zirconocene‐based porous coordination cages. With a linear ditopic ligand, the zirconocene‐based cluster can form either a capsular or a tetrahedral cage. The interconversion mechanism behind the formation of the two cages as well as the utilization of external stimuli for the manipulation of the conversion equilibria is explored.